Chemical Doping: Chemically Tuned p‐ and n‐Type WSe2 Monolayers with High Carrier Mobility for Advanced Electronics (Adv. Mater. 42/2019). Issue 42 (15th October 2019) - Ji, Hyun Goo; Solís‐Fernández, Pablo; Yoshimura, Daisuke; Maruyama, Mina; Endo, Takahiko; Miyata, Yasumitsu; Okada, Susumu; Ago, Hiroki
Abstract : In article number1903613, Hiroki Ago and co‐workers demonstrate the chemical‐doping‐induced conversion of ambipolar WSe2 monolayers to p‐ and n‐type semiconductors. The chemical doping not only allows control over the main carriers, but also significantly increases the carrier mobility. By integrating the chemically doped WSe2, a CMOS inverter and an in‐plane p–n junction with superior performance are successfully fabricated.